1999
DOI: 10.1016/s0896-6273(00)80737-0
|View full text |Cite
|
Sign up to set email alerts
|

Control of Recruitment and Transcription-Activating Function of CBP Determines Gene Regulation by NMDA Receptors and L-Type Calcium Channels

Abstract: Recruitment of the coactivator CBP by signal-regulated transcription factors and stimulation of CBP activity are key regulatory events in the induction of gene transcription following Ca2+ flux through ligand- and/or voltage-gated ion channels in hippocampal neurons. The mode of Ca2+ entry (L-type Ca2+ channels versus NMDA receptors) differentially controls the CBP recruitment step to CREB, providing a molecular basis for the observed Ca2+ channel type-dependent differences in gene expression. In contrast, act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
199
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(210 citation statements)
references
References 52 publications
9
199
0
1
Order By: Relevance
“…Together, these results suggest that although upstream signaling events appear normal, resulting in CREB phosphorylation, without CBP there is a failure to activate cfos expression. This uncoupling between phospho-CREB and CREB:CBP-mediated gene expression is similar to previous observations showing this dissociation in cell culture (Chawla et al, 1998;Hardingham et al, 1999).…”
Section: Creb Phosphorylation Is Uncoupled From Creb:cbp-mediated Gensupporting
confidence: 91%
See 2 more Smart Citations
“…Together, these results suggest that although upstream signaling events appear normal, resulting in CREB phosphorylation, without CBP there is a failure to activate cfos expression. This uncoupling between phospho-CREB and CREB:CBP-mediated gene expression is similar to previous observations showing this dissociation in cell culture (Chawla et al, 1998;Hardingham et al, 1999).…”
Section: Creb Phosphorylation Is Uncoupled From Creb:cbp-mediated Gensupporting
confidence: 91%
“…In the late 1990s, two studies demonstrated that the phosphorylation of CREB could be uncoupled from CREBmediated gene expression (Chawla et al, 1998;Hardingham et al, 1999). Chawla et al (1998) proposed a model in which CREB:CBP-mediated gene expression requires two steps: The phosphorylation of CREB (resulting in the recruitment of CBP) and the phosphorylation of CBP for its activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e, f, The level of p-CREB was greatly attenuated in SL327-treated rats compared with DMSO controls. Nordheim, 1996) and plays a key role in calcium-mediated gene transcription in cellular models of plasticity (Hardingham et al, 1999;Hu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…CREB also plays a central role in memory formation (West et al ., 2001). The transcriptional activation of CREB is crucially dependent on phosphorylation of Ser133 by kinases such as Ca 2+ /calmodulin kinase (CaMK), ras/mitogen‐activated protein kinase (MAPK), ERK1/2 (Wu et al ., 2001), and protein kinases A and C (Hardingham et al ., 1999). Extracellular signal‐regulated kinases (ERKs) are key genes in activating survival pathways (Roskoski, 2012), and their transient activation plays an important role in memory‐related processes (Costa & Silva, 2002).…”
Section: Introductionmentioning
confidence: 99%